Comparison of the Volatile Constituents of Thymus serpylum from the Altitude of Far Western Nepal & North India - Thakuri, BC; Padalia, RC; Mathela, CS (Scientific World, 2010)
The composition of aerial parts of the Thymus Serpylum family Labiatae, collected from two localities in Uttarakhand of India viz., Martoli village (3600 m), Jageshwar (1500 m) and one locality from Dadeldhura district of far western Nepal (1900 m) are reported. The steam-distilled essential oils have been investigated for its flavor constituents by GC and GC-MS. Seventeen compounds representing (88.16%), twenty compounds representing (97.03%) & seventeen compounds (96.13%) respectively from Martoli village, Jageshwar and Dadeldhura have been identified. The collection from Martoli village contained thymol (68.32%) along with carvacrol (7.19%) as major constituents and the sample collected from Dadeldhura is also rich in thymol (74.92%) and carvacrol (5.09%). However, the sample from Jageshwar had reduced amount of thymol (46.24%) along with significant quantities of ã-terpinene (12.21%), thymoquinone (9.43%), p-cymene (7.30%) and considerably reduced amount of carvacrol (4.62%). The Nepali (Dadeldhura) sample is good source of thymol. Key words: Thymus serpylum; Labiatae; Composition of volatile constituents; Dadeldhura; Thymol; Carvacrol; Thymoquinone; P-cymene. DOI: 10.3126/sw.v7i7.3834 Scientific World Vol.7(7) 2009 pp.92-93